Performance evaluation methods in the hotel industry - Nunes, Catarina Rosa (2024)
This paper aims to contribute to increasing knowledge of performance evaluation methods used by the hotel industry, analysing whether there is a link between hotel characteristics and evaluation methods used. To achieve this goal we conducted surveys and interviews with financial officers of 275 four and five star hotels located in Portugal. The results support the conclusion that there is a link between hotel characteristics and performance evaluation methods used.